Comparison of transcriptome responses to glyphosate, isoxaflutole, quizalofop-p-ethyl and mesotrione in the HepaRG cell line. (2018) - Mesnage, Robin; Biserni, Martina; Wozniak, Eva; Xenakis, Theodoros; Mein, Charles A.; Antoniou, Michael N.
Highlights: We evaluated glyphosate, isoxaflutole, quizalofop-p-ethyl and mesotrione. Gene expression alterations were measured in the HepaRG liver cell line. Quizalofop-p-ethyl was the most toxic, causing alterations in lipid metabolism. Isoxaflutole was less toxic, but was revealed as a possible PXR activator. Glyphosate and mesotrione only caused subtle changes in transcriptome profiles. Abstract: Use and thus exposure to quizalofop-p-ethyl, isoxaflutole, mesotrione and glyphosate, which are declared as active principles in commercial formulations of herbicides, is predicted to rapidly increase in coming years in an effort to overcome the wide-spread appearance of glyphosate-resistant weeds, especially in fields where glyphosate-tolerant genetically modified crops are cultivated in the USA. Thus, there is an urgent need for an evaluation of metabolic effects of new pesticide ingredients used to replace glyphosate. As the liver is a primary target of chemical pollutant toxicity, we have used the HepaRG human liver cell line as a model system to assess the toxicological insult from quizalofop-p-ethyl, isoxaflutole, mesotrione and glyphosate by determining alterations in the transcriptome caused by exposure to three concentrations of each of these compounds, including a low environmentally relevant dose. RNA-seq data were analysed with HISAT2, StringTie and Ballgown. Quizalofop-p-ethyl was found to be the most toxic of the pesticide ingredients tested, causing alterations in gene expression that are associated with pathways involved in fatty acid degradation and response to alcoholism. Isoxaflutole was less toxic, but caused detectable changes in retinol metabolism and in the PPAR signalling pathway at a concentration of 1 mM. ToxCast data analysis revealed that isoxaflutole activated PPAR gamma receptor and pregnane X responsive elements in reporter gene assays. Glyphosate and mesotrione caused subtle changes in transcriptome profiles, with too few genes altered in their function to allow a reliable pathway analysis. In order to explore the effects of glyphosate in greater depth and detail, we undertook a global metabolome profiling. This revealed a decrease in free long chain fatty acids and polyunsaturated fatty acid levels at the lowest concentration (0.06 μM) of glyphosate, although no effects were detected at the two higher concentrations tested, perhaps suggesting a non-linear dose response. This surprising result will need to be confirmed by additional studies. Overall, our findings contribute to filling the knowledge gap regarding metabolic toxicity that can potentially arise from exposure to these four herbicide active principles.